Synthesis and biological activity of 5-(4-methoxyphenyl)-oxazole derivatives. Issue 2 (15th January 2015) - Yamamuro, Daisuke; Uchida, Ryuji; Ohtawa, Masaki; Arima, Shiho; Futamura, Yushi; Katane, Masumi; Homma, Hiroshi; Nagamitsu, Tohru; Osada, Hiroyuki; Tomoda, Hiroshi
Graphical abstract